EFEKTIVITAS SCIENCE VIDEO PROJECT-BASED LEARNING SEBAGAI STIMULAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA - Mochammad Maulana Trianggono; Moh Usman Kurniawan; Firman Ashadi (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
Technological developments in the digital era as it is today show a high trend of increasing video production, both as entertainment and as learning. This euphoria should be used positively by educators in stimulating the creativity of students. The purpose of this study was to describe the development of students' creative thinking skills through the project of making science learning videos for early childhood. This research design uses true experimental research – pretest-posttest group design. The results of this study were analyzed quantitatively-descriptively using the n-gain analysis approach based on the results of the assessment of students' creative thinking skills in making science learning videos for early childhood. Independent t-test analysis was also used to analyze the significance of the difference in the n-gain score between science video project-based learning and learning with ordinary presentations (with power point). The results showed that the science video project-based learning could effectively stimulate students' creative thinking skills with an n-gain score of 0.62 with medium category. Independent t-test analyze result also showed that there was a significant difference between the n-gain scores between science video project-based learning and learning with power point based presentations.